2010
DOI: 10.1152/ajpregu.00747.2009
|View full text |Cite
|
Sign up to set email alerts
|

Endonuclease G does not play an obligatory role in poly(ADP-ribose) polymerase-dependent cell death after transient focal cerebral ischemia

Abstract: Activation of poly(ADP-ribose) polymerase (PARP) and subsequent translocation of apoptosis-inducing factor contribute to caspase-independent neuronal injury from N-methyl-d-aspartate, oxygen-glucose deprivation, and ischemic stroke. Some studies have implicated endonuclease G in the DNA fragmentation associated with caspase-independent cell death. Here, we compared wild-type and endonuclease G null mice to investigate whether endonuclease G plays a role in the PARP-dependent injury that results from transient … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Endonuclease G, which induces nuclear DNA fragmentation during apoptosis, is also released from mitochondria following cerebral ischemia (Nielsen et al, 2008). However, endoG-deficient mice were still sensitive to prolonged I/R (Xu et al, 2010). …”
Section: Mechanisms Underlying I/r Injurymentioning
confidence: 99%
“…Endonuclease G, which induces nuclear DNA fragmentation during apoptosis, is also released from mitochondria following cerebral ischemia (Nielsen et al, 2008). However, endoG-deficient mice were still sensitive to prolonged I/R (Xu et al, 2010). …”
Section: Mechanisms Underlying I/r Injurymentioning
confidence: 99%
“…Indeed, pharmacologic or genetic inhibition of Omi/HtrA2 attenuates postischemic death by apoptotic mechanisms (419, 590), but such approaches have not yet been used to more clearly define a causal role for Smac/DIABLO in I/R injury. Although cerebral ischemia induces release of mitochondrial endonuclease G (588), mice genetically deficient in this inducer of nuclear DNA fragmentation during apoptosis retained their sensitivity to prolonged I/R (864). …”
Section: Several Modes Of Cell Death Are Induced By I/rmentioning
confidence: 99%
“…This uncoupling can also occur by dissociation of NOS from associated proteins (e.g., HSP90) that are necessary for coupled function, oxidation of BH 4 secondary to overproduction of O 2 − or ONOO − , oxidation of the zinc-thiolate complex that stabilizes the NOS homodimer, or via S-glutathionylation (663). NOS uncoupling appears to be an important contributor to I/R injury, and can be reversed by administration of L-arg, BH 4 , or the BH 4 precurser sepiaterin in animal models (212, 663, 708, 864). …”
Section: Mechanisms Underlying I/r Cell Injury and Deathmentioning
confidence: 99%
“…S1C); thus, EndoG is unlikely to be the main contributor to PARP-1–dependent large DNA fragmentation and MNNG-induced cell death (fig. S1) (13, 15). …”
Section: Parp-1–dependent Cell Death Requires Mifmentioning
confidence: 99%
“…AIF itself has no obvious nuclease activity (2). Although it has been suggested that CED-3 protease suppressor (CPS)–6, an endonuclease G (EndoG) homolog in Caenorhabditis elegans , cooperates with the worm AIF homolog (WAH-1) to promote DNA degradation (12), mammalian EndoG does not seem to have an essential role in PARP-dependent chromatinolysis and cell death (13, 14) and after transient focal cerebral ischemia in mammals (15). Thus, the nuclease responsible for the chromatinolysis during parthanatos is not known.…”
mentioning
confidence: 99%